Effects of sulphur on the storage stability of the bio and fossil fuel blends - Sirviö, Katriina; Niemi, Seppo; Heikkilä, Sonja; Hiltunen, Erkki (Estonian Agricultural University, Faculty of Agronomy, 2017)
In this study, the aim was to find out if mixing two common fuels together could be beneficial for both the environment and storage stability of fuel. It is obvious, that adding biodiesel to fossil fuel will decrease its sulphur content and reduce its carbon monoxide and hydrocarbon, sulphur dioxide and soot emissions. But will the high sulphur content enhance the storage stability of the biodiesel? Four B20 samples were produced, consisting of 20 vol% biodiesel and 80 vol% fossil diesel. The samples were prepared from rapeseed methyl ester (RME), low sulphuric fossil diesel fuel and high sulphuric diesel solvent. The blends had different sulphur contents of 6, 76, 149 and 226 mg kg-1. For these B20 fuel samples, the parameters were compared that correlate with the storage stability of the fuel blends. The studied parameters were the oxidation stability (OSI, according to EN 15751:2015), acid number (AN, according to EN 14104:2003) and kinematic viscosity (KV, by Stabinger SVM 3000 rotational viscometer). The measurements were carried out straight after mixing the blends, and again after 4, 8 and 12 weeks. According to the results, the fuel containing less sulphur slightly lost its oxidation stability within three months. Instead, the oxidation stability of high sulphuric samples improved within the same time frame. As a conclusion, the study gave a reason to assume that – in spite of its known drawbacks – the sulphur may be favourable to fuel blends’ storage stability but the phenomenon and chemistry should be studied in more detail.
Keywords: biofuel; blending; FAME; diesel fuel; B20; stability; sulphur; fi=Energiatekniikka|en=Energy Technology|